PENGARUH KOMITMEN, KEMAMPUAN DAN MOTIVASI TERHADAP PRESTASI KERJA APARAT KANTOR DESA SELAT AKAR KECAMATAN TASIK PUTRI PUYU - Arifudin; Mei Indrawati; C. Sri Hartati (Journal of Applied Management and Accounting Science, 2021)
The target of this research is to provide an overview and analysis of the impact between commitment, ability and motivation on the work performance of the Selat Akar Village Office Apparatus, Tasik Putri Puyu District. The research approach is included in the quantitative research approach. The population is 31 officers from Selat Akar Village Office, Tasik Putri Puyu District and the number of samples is 30 people using census sampling technique. The method of collecting data is using questionnaires and documentation. The data analysis technique in this study used multiple linear regression analysis. The findings in the research found that the commitment and work ability of the officers were in fairly good condition, while the motivation and work performance of the officers at the Selat Akar Village Office were in good condition. There is no significant impact between ability on work performance while there is a significant impact between ability or motivation on work performance of the Selat Akar Village Office Apparatus, Tasik Putri Puyu District.